2017
DOI: 10.1111/jcmm.13294
|View full text |Cite
|
Sign up to set email alerts
|

Systemic administration of bone marrow‐derived cells leads to better uterine engraftment than use of uterine‐derived cells or local injection

Abstract: Stem cells are recruited to the uterus where they differentiate into endometrial cells and have been suggested as potential therapy for uterine injury such as Asherman's syndrome. However, it is unknown whether local intrauterine injection may result in better stem cell engraftment of the uterus compared with systemic administration, and whether uterine‐derived cells (UDCs) may confer an advantage over BM‐derived cells (BMDCs). Mice underwent local injury to a single uterine horn. Green fluorescent protein (GF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 45 publications
(78 reference statements)
2
49
0
Order By: Relevance
“…Determining the ideal routes of administration for various DMD therapies have proven to be a challenge [11,12]. Though there is scarce literature comparing routes of stem cell administration in the mdx mice for treatment of DMD cardiomyopathy, studies using a murine model for Ashermann's syndrome have shown systemic administration of bonemarrow derived stem cells led to better stem cell engraftment in uterus, leading to improved fertility when compared with local intrauterine injection [53]. Based on our experience, with the systemic-intraosseous injection of bone marrow cells and chimeric cells showing better engraftment and maintenance of the donor derived chimerism [43,45,46], in this study, we focused on systemic administration of DEC through intraosseous injection, as this facilitates the process of systemic delivery and potential engraftment to other muscles including the cardiac muscle as confirmed in this study by increased dystrophin expression and reduced fibrosis which correlated with significant improvement of EF and FS on echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…Determining the ideal routes of administration for various DMD therapies have proven to be a challenge [11,12]. Though there is scarce literature comparing routes of stem cell administration in the mdx mice for treatment of DMD cardiomyopathy, studies using a murine model for Ashermann's syndrome have shown systemic administration of bonemarrow derived stem cells led to better stem cell engraftment in uterus, leading to improved fertility when compared with local intrauterine injection [53]. Based on our experience, with the systemic-intraosseous injection of bone marrow cells and chimeric cells showing better engraftment and maintenance of the donor derived chimerism [43,45,46], in this study, we focused on systemic administration of DEC through intraosseous injection, as this facilitates the process of systemic delivery and potential engraftment to other muscles including the cardiac muscle as confirmed in this study by increased dystrophin expression and reduced fibrosis which correlated with significant improvement of EF and FS on echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…A certain degree of overlap may exist in both cell populations, and in situ fate determination of CD44 + cells by lineage tracing will reveal whether they can self-renew and differentiate into the complete uterine epithelial lineage as these uterine epithelial stem cells do. In addition to these proposed resident cell sources, the exogenous supply of bone marrow cells, through tissue transplantation from a donor animal, has led to the suggestion that bone marrow cells are able to contribute to uterine regeneration (12,36). Whether or not the conditions experienced by the uterus during tissue transplantation reflect physiological conditions will be critical in determining if such an exogenous cellular supply plays a role in supporting normal cyclical uterine regeneration, which the current study is focused on.…”
Section: Discussionmentioning
confidence: 99%
“…Nor is it clear whether such phenotypic characteristics would be seen in uterine stem cells. In vitro clonogenicity assays and transplantation have also been applied to search for potential uterine stem cells (2,(11)(12)(13), but evidence is lacking that the in vivo counterparts of these candidate cells behave like stem or progenitor cells. Mapping of the fate determination of these claimed stem or progenitor cell candidates during normal uterine cycling is required to define their stem cell potential.…”
mentioning
confidence: 99%
“…The human endometrium is a dynamic remodeling tissue that undergoes over 400 cycles of growth, differentiation, and shedding of endometrial cells during the reproductive period [ 1 2 ]. This physiology is mainly regulated by the effects of sex steroid hormones and other biological molecules, and is essential for implantation and pregnancy in mammals.…”
Section: Introductionmentioning
confidence: 99%